Antimycobacterial evaluation and preliminary phytochemical investigation of selected medicinal plants traditionally used in Mozambique - Luo, Xuan (2013)
Ethnopharmacological relevance Several medicinal plants are traditionally used in Mozambique to treat tuberculosis and related symptoms. Aims of the study It was aimed to assess the in vitro antimycobacterial activity of crude extracts from fifteen medicinal plants and to reveal main classes of compounds which may account for the activity of extracts. Methods and materials The plant materials were sequentially extracted by n-hexane, dichloromethane, ethyl acetate, and 70% ethanol. Decoction of each plant material was also prepared according to traditional use. Broth microdilution method was employed to screen extracts against two mycobacterial species: Mycobacterium smegmatis ATCC 607 and Mycobacterium tuberculosis H37Rv. The extracts with minimum inhibitory concentration(s) (MIC) below 125 μg/mL were considered active and further tested against different mycobacterial species and strains, namely Mycobacterium tuberculosis H37Ra, Mycobacterium bovis BCG ATCC 35734, Mycobacterium smegmatis mc2 155, Mycobacterium avium DSM 44156 and DSM 44157. Cytotoxic effect was evaluated against human macrophages from the monocytic THP-1 cells. Main classes of compounds in these active extracts were proposed from their 1H NMR spectroscopic characterizations. Results n-Hexane extracts of Maerua edulis and Securidaca longepedunculata, ethyl acetate extract of Tabernaemontana elegans and dichloromethane extract of Zanthoxylum capense were found to possess considerable activity against Mycobacterium bovis BCG and Mycobacterium tuberculosis H37Ra with MIC 15.6–62.5 μg/mL. Tabernaemontana elegans ethyl acetate extract displayed strong activity against Mycobacterium tuberculosis H37Rv (MIC 15.6 μg/mL). Except for Tabernaemontana elegans ethyl acetate extract which presented potent cytotoxic effects in THP-1 cells (IC50 < 4 μg/mL), the other three plant extracts showed moderate to none toxicity. Based on 1H NMR spectroscopic analysis, major components in both Maerua edulis and Securidaca longepedunculata n-hexane extracts were linear chain unsaturated fatty acids. Zanthoxylum capense dichloromethane extract contained more complex constituents (mostly phenolic compounds). In the most potent extract, Tabernaemontana elegans ethyl acetate extract, the prominent compounds were identified as indole alkaloids. Conclusions The pronounced antimycobacterial activity of the medicinal plants Maerua edulis, Securidaca longepedunculata, Zanthoxylum capense, and Tabernaemontana elegans suggested that they might provide compounds which could be potential anti-TB drug leads.